2005
DOI: 10.1196/annals.1345.066
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Candidate Modifier Polymorphisms in Hb E‐β0‐Thalassemia Patients

Abstract: Hemoglobin E (Hb E)-beta-thalassemia patients display a range of clinical severities, from nearly asymptomatic to transfusion-dependent thalassemia major. Given this clinical heterogeneity, additional genetic factors modifying disease severity remain to be discovered. Association studies are being conducted to elucidate the role of genetic polymorphisms as disease severity modifiers in Hb E-beta-thalassemia patients. Using strict scoring criteria, 1060 Hb E-beta-thalassemia patients were categorized into mild,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 9 publications
0
13
0
4
Order By: Relevance
“…Several genotype-phenotype studies exploring the association between the AHSP gene and severity of thalassemia could not identify any correlation. [26][27][28] However, Bhattacharya et al 22 reported an increase of AHSP expression in thalassemic erythrocytes, which likely represents the original the source of AHSP for EVs.…”
Section: Discussionmentioning
confidence: 99%
“…Several genotype-phenotype studies exploring the association between the AHSP gene and severity of thalassemia could not identify any correlation. [26][27][28] However, Bhattacharya et al 22 reported an increase of AHSP expression in thalassemic erythrocytes, which likely represents the original the source of AHSP for EVs.…”
Section: Discussionmentioning
confidence: 99%
“…Triplicated or quadruplicated α-globin genes increase the severity of E-thalassemia and occur in approximately 4% of the population. [7,8] The clinical course of E β-thalassemia is punctuated by acute and chronic complications that may cause serious morbidity and mortality. The marked expansion of erythropoiesis is responsible for much of the pathology of the disease including hepatosplenomegaly, extramedullary haematopoietic masses, growth retardation, delayed sexual maturation and bone deformities.…”
Section: Discussionmentioning
confidence: 99%
“…11 Semakin berat derajat thalassemia maka semakin berat proses hemolisis sehingga semakin bergantung pada transfusi darah dan meningkatkan risiko penumpukan besi. 12,13 Tipe thalassemia intermedia yang non-dependent transfusion terjadi hemolitik kronik berkepanjangan, peningkatan aktivitas prokoagulan kronis, dan akumulasi besi akibat peningkatan absorpsi besi intestinal dibandingkan dengan tipe thalassemia mayor. 14,15 Kadar hemoglobin yang lebih rendah terjadi akibat proses hemolitik yang lebih hebat.…”
unclassified
“…22 Derajat thalassemia terdiri atas derajat ringan, sedang, dan berat. 12 Tipe thalassemia terdiri atas thalassemia mayor dan intermedia.…”
unclassified